Analysis Of Healthcare Workers Satisfaction With Electronic Medical Records At Jimbaran I Primary Health Care - Dewa Ayu Cantika Pradyna Dewi; Ika Setya Purwanti; Putu Ayu Sri Murcittowati (International Journal of Health Engineering and Technology, 2026)
The development of digital technology in the health sector encourages health facilities to implement Electronic Medical Records (EMR). The success of EMR implementation depends on the satisfaction of health workers as system users. Based on preliminary observations at Jimbaran I Sub-district Health Center, several obstacles were found, including limited human resources, system disruptions, and lack of IT personnel. These conditions may affect user satisfaction and service effectiveness. This study aims to determine the level of health worker satisfaction with the use of Electronic Medical Records based on the End User Computing Satisfaction (EUCS) method. This research uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The subjects of this study were eight health workers consisting of doctors, nurses, registration officers, and midwives. The results showed that health workers were generally satisfied with the use of Electronic Medical Records in terms of content, accuracy, format, ease of use, and timeliness. However, there are still obstacles related to system adaptation and data input accuracy during busy service hours.